Development of the system architecture for design works automation - Zakharchenko, Viktoriia; Nenia, Viktor (Eastern-European Journal of Enterprise Technologies, 2016)
The analysis of the current state of development of the systems for design works automation (CAD systems) showed the insufficient development both of the system functioning management in general, and of the management of the design procedures performance. System analysis of the design process as an automation subject is carried out. Taking into account requirements of continuous development of the system for design works automation, the separate interaction channels with developers of CAD system components in the structure of this system are provided. The technique of the design procedures organization is offered. The same performance of design procedures on different design stages and phases, the formation of ToR for the design and tasks for the performance of design procedures are provided. This approach provides the organization of the design process and its software and information support, the possibility of design works accounting, the monitoring of their status and management of them. The description of components of the information system for the application automation of CAD elements is provided. The system includes databases units. They consist of contracts description, description of project structure, ToR for the design of technical objects, description of designed objects structure, description of tasks for the design of designed object components and the log-book of the performed tasks for design works with different powers to data access. Necessary information flows and the sequence of their implementation for the organization of the design process of technical objects are defined. Separate units make templates of design documents, current and completed design solutions. The need of existence of three types of the functional software is revealed: the monitoring program of a system status, the client program of a system user and the package of applied design programs. The charts of interaction between designers and the design system and between the system elements among themselves during the design works performance are provided. Thus, the conceptual structure of the system for the organization of the process of the computerized technical objects design and the management of developers during the implementation of this process are offered.